Case Report: Fatal Neurotoxicity Following Resmethrin Poisoning in a Child - Huang, Lilin; Peng, Shumei; Li, Ronghan; Huang, Dongping; Xie, Danyu (Frontiers in Pediatrics, 2021)
Resmethrin, a type I pyrethroid insecticide, can activate sodium channels, causing neurotoxicity in both mammals and insects. Possible routes of poisoning include inhalation, dermal contact and ingestion. There are no specific symptoms for resmethrin poisoning. Until now, no antidote has been available for resmethrin. Resmethrin poisoning is rarely reported in children. Here, we report a fatal case of resmethrin poisoning that might have been caused by accidental ingestion by a 26-month-old child. He presented with neurotoxic symptoms that included vomiting, recurrent seizures, and coma. The cranial CT showed extensive lesions of low intensity in the bilateral white matter, thalamus, brainstem, and cerebellum. Lumbar punctures showed increased intracranial pressure (ICP>25 mmHg). Cerebrospinal fluid (CSF) tests revealed that protein was elevated to 289.2 mg/dL without pleocytosis. Resmethrin was detected in his blood by liquid chromatography-mass spectrometry, which confirmed the diagnosis of resmethrin poisoning. The child developed brain stem herniation and then was declared brain dead at the 77th hour after admission. Resmethrin poisoning can be fatal, and it requires immediate diagnosis and treatment. Previous studies reported that cranial CT and CSF analyses were all normal in patients with pyrethroid poisoning. This case might extend the knowledge of neuroimaging and CSF analysis in children with resmethrin poisoning.